Strategi Pengembangan Usaha Pada Rumah Pangan Kita Menggunakan Business Model Canvas (BMC) - Risnaningsih, Inne (Koaliansi : Cooperative Journal, 2023)
This research was conducted at Rumah Pangan Kita (RPK). The purpose of this research is to determine business development strategy in RPK used business model canvas based on nine blocks assisted by SWOT analysis. The analysis results show RPS is in quadran 3, that is support the strategy of exploiting opportunities through good promotion takes the form of getting closer to company with local communities by holding events, sports, matches; keep maintaining and improving good services with local communities and consumers and adding human resources to support operational activities so that demand is met to the fullest.